Serangan Masif Artificial Intelligence Pada Sumber Daya Manusia: Pengaruh Dan Dampak Psikologi Generasi Z (1997 – 2012): Studi Kasus Pada Subjek IN-01 - Tan Evan Tandiyono (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The era of globalization that we are living in has brought major changes in various aspects of human life. In the midst of the era of globalization, new challenges and opportunities emerge. Society is becoming more open to different cultures and world views. The birth of artificial intelligence (AI) has become a historical milestone that defines the journey of human technology. However, the role of AI is not only limited to the business sector. In everyday life, we interact with virtual assistants, recommendation systems, and other AI technologies. Qualitative research is a research approach that aims to understand and explain social phenomena through in-depth analysis of non-numerical data. This research method is more inductive, where theory develops as data is collected and analyzed. The data collection process in qualitative research involves direct interaction with participants (interviews and FGDs), in-depth observation, or data analysis. Qualitative data analysis involves the process of coding, categorizing, and organizing patterns of findings. Using qualitative analysis software such as NVivo or Atlas.ti can make complex data management and analysis easier. The time period used in this research is 4 months, starting September 2023 – December 2023. The research results show that AI can have both positive and negative influences on Generation Z. Apart from that, AI is also able to have positive and negative impacts on Generation Z. This research even shows extraordinary and unexpected findings.